Assessing Competencies: "What Have You Done for Me Lately?"1. (December 2015) - Klonoff, Elizabeth A.
Abstract : The assessment of trainees in health professions has changed dramatically in recent years. Virtually every field has moved from the simple testing of knowledge to an approach involving the assessment of competencies, and health service psychology is no exception. It is more than just a little ironic, then, that the field that prides itself on setting the standard for what constitutes adequate assessment has lagged so far behind other health professions in developing procedures for conducting these assessments. The purpose of the current article is to raise four major questions about competency assessment in health service psychology. First, how should these competencies be defined? Second, what are the outcomes that should derive from successful achievement of these competencies? Third, when should these competencies be evaluated, and who should do the evaluating? Finally, where might this move to competency assessment lead us in the future?